Knowledge Sharing and Innovative Work Behaviour in Healthcare: A Micro‐Level Investigation of Direct and Indirect Effects. Issue 4 (17th October 2014) - Radaelli, Giovanni; Lettieri, Emanuele; Mura, Matteo; Spiller, Nicola
<x xml:space="preserve">Abstract</x> This study presents a micro‐level investigation that provides new insights into how employees' knowledge sharing affects their own innovative work behaviours (IWBs). Our study posited three mechanisms linking an individual's knowledge sharing behaviours to his or her own IWBs: (i) a direct effect whereby the act of sharing elicits a recombination and translation of knowledge that facilitates innovation; (ii) an indirect effect whereby knowledge sharing creates social conditions (i.e., reciprocation with new knowledge) for innovation; (iii) a distal effect whereby the antecedents of knowledge sharing also promote innovation. We tested these hypotheses on 155 employees in four palliative care organizations. Our results provide original evidence that employees who share knowledge also engage more in creating, promoting and implementing innovations. This study reveals a direct, unmediated link between knowledge sharing behaviours and IWBs. Our evidence suggests that it is the act of knowledge recombination and translation embedded in knowledge sharing that exerts the most positive effect on IWBs. We discuss how this result indicates that sharing knowledge ignites transformation and exploitation capabilities that help sharers innovate their own work practices.